Project-based learning module on creativity and entrepreneurship product subjects: Validity and empirical effect - Aziz, Wildan Abdul; Wulansari, Rizky Ema; Putra, Randi Purnama; Tun, Hla Myo; Tin, Chau Trung; Ya, Kyaw Zay (Universitas Negeri Padang, 2023)
The learning process of Creativity and Entrepreneurship Product subjects in Vocational High Schools still uses printed books, resulting the students’ boredom in learning the materials. Apart from that, the learning method used is the lecture method which is certainly less effective in supporting students' understanding on the materials so that learning is more teacher-centered. Meanwhile, the demand for the Emancipated Curriculum is that learning must be student-centered. This study aimed to develop learning tools for PjBL-based teaching module on the Creativity and Entrepreneurship Product subjects. This research was a research and development using the ADDIE development model. There were 12 experts who validated this module from 3 aspects, including material, media and model, and language aspects, and 30 students as participants for pilot study. The results of this research showed that this module is valid and has positive effects in supporting the learning process for the Creativity and Entrepreneurship Product subjects. This study brings pedagogical implications for the effectiveness of Creativity and Entrepreneurship Product subjects and is a method that can be implemented by teachers in the subject learning.